2021
DOI: 10.3389/fcell.2021.678282
|View full text |Cite
|
Sign up to set email alerts
|

Histone Arginine Methyltransferase CARM1-Mediated H3R26me2 Is Essential for Morula-to-Blastocyst Transition in Pigs

Abstract: Coactivator-associated arginine methyltransferase 1 (CARM1) is involved in both establishment of first pluripotent lineage and pluripotency maintenance of embryonic stem cells (ESCs) in mice. However, the histone substrates and role of CARM1 in early embryonic development remain largely unknown. Here, we show that CARM1 specifically catalyzes H3R26me2 to promote porcine blastocyst formation. The putative histone substrates of CARM1, including H3R2me2, H3R17me2, and H3R26me2, are present in pig early embryos. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“… 108 Carm1, which specifically catalyzes H3R26me2, was reported to participate in blastocyst development of porcine embryos. 109 Mier1 functions as a transcriptional repressor by recruitment of Hdac1 and has a similar expression change as Mta2, demonstrating that histone deacetylases (HDACs) are indispensable for ZGA by creating correct transcriptionally repressive and active states. 110 The functions of Mier1 and Nsd1b in regulating the MZT of zebrafish embryos are still not clear.…”
Section: Resultsmentioning
confidence: 99%
“… 108 Carm1, which specifically catalyzes H3R26me2, was reported to participate in blastocyst development of porcine embryos. 109 Mier1 functions as a transcriptional repressor by recruitment of Hdac1 and has a similar expression change as Mta2, demonstrating that histone deacetylases (HDACs) are indispensable for ZGA by creating correct transcriptionally repressive and active states. 110 The functions of Mier1 and Nsd1b in regulating the MZT of zebrafish embryos are still not clear.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that DDAH2 protein is elevated in both cortical and hippocampal lysates in 3xTg-AD animals, which may be a compensatory response to increased ADMA production which was also observed in 3xTg-AD animals (Figure 3a,b). The most well-known function of PRMT4 is the methylation of histone H3 (Cao et al, 2021). The role of PRMT 4 in the central nervous system is primarily involved in the development of astroglial and oligodendritic cells (Selvi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The asymmetrical distribution of H3R26me2 in blastomeres is detected in embryos as early as the four-cell stage [153]. Blastomeres with higher levels of CARM1 and H3R26me2 contribute more significantly to the formation of the ICM [159]. Furthermore, higher levels of H3R26me2 enhance the expression of pluripotent genes and facilitate Sox2 binding to its targets, contributing to ICM specification.…”
Section: Histone H3r26me2: Pivotal In Cell Fate Determination In Embryosmentioning
confidence: 99%
“…Furthermore, higher levels of H3R26me2 enhance the expression of pluripotent genes and facilitate Sox2 binding to its targets, contributing to ICM specification. Additionally, CARM1 overexpression can increase the frequency of asymmetric cell divisions, leading cells to adopt a more internal position in the embryo [159]. Alongside CARM1, another chromatin regulator named PR domain-containing 14 (PRDM14) is also asymmetrically expressed in four-cell embryos, thus modulating the level of H3R26me2 to favor contribution to the ICM [160][161][162].…”
Section: Histone H3r26me2: Pivotal In Cell Fate Determination In Embryosmentioning
confidence: 99%